Peningkatan Pembelajaran Servis Bawah Bola Voli Menggunakan Metode Group Investigation (GI) - Lamasese, Teguh Firmansyah; Datau, Suriyadi; Tumaloto, Ella H (Universitas Negeri Gorontalo, 2025)
This research aims to improve basic underhand serve techniques in volleyball using the Group Investigation (GI) method. The data from classroom action research with grade VII-A students at SMP Negeri 1 Molibagu was collected in two cycles. Each cycle consisted of four stages: (1) Planning, (2) Implementation, (3) Observation and Interpretation, and (4) Analysis and Reflection. Learning through the Group Investigation (GI) method can improve the learning outcomes of underhand serves in volleyball among grade VII-A students at SMP Negeri 1 Molibagu. The analysis showed significant improvement in cycle I, and a significant increase in cycle II. The learning outcomes for volleyball underhand serves in cycle I were 67.73%, and in cycle II, there was an increase to 81.84% in student learning outcomes, with a total of 29 students.